2016
DOI: 10.1111/inr.12342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nurse work environment on job dissatisfaction, burnout, intention to leave

Abstract: Background The nursing shortage is a critical issue in many countries. High turnover rates among nurses is contributing to the shortage, and job dissatisfaction, intention to leave, and burnout have been identified as some of the predictors of nurse turnover. A well‐established body of evidence demonstrates that the work environment for nurses influences nurse job dissatisfaction, intention to leave, and burnout, but there never has been a study undertaken in Thailand to investigate this relationship. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
260
5
34

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(329 citation statements)
references
References 42 publications
30
260
5
34
Order By: Relevance
“…Findings in our study showed that “adequate human and material resources” (M = 2.83, SD = 0.69) and “nurse participation in hospital affairs” (M = 3.16, SD = 0.57) scored lowest by the respondents, which were consistent with the findings of other studies (Nantsupawat et al, ; Panagiotis, Peter, & Ioannis, ). Nursing shortage is a global problem, especially for nurses with a master's or doctoral degree.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Findings in our study showed that “adequate human and material resources” (M = 2.83, SD = 0.69) and “nurse participation in hospital affairs” (M = 3.16, SD = 0.57) scored lowest by the respondents, which were consistent with the findings of other studies (Nantsupawat et al, ; Panagiotis, Peter, & Ioannis, ). Nursing shortage is a global problem, especially for nurses with a master's or doctoral degree.…”
Section: Discussionsupporting
confidence: 92%
“…The highest scores for “collegial nurse‐physician relations” (M = 3.36, SD = 0.51) were found in this study, which were consistent with the findings from another study conducted among registered nurses (Nantsupawat et al, ; Zhang et al, ). A systematic review showed positive correlations between collaboration and teamwork with error reduction and patient safety improvement (Kilner & Sheppard, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Neste modelo, a predominância do modelo biomédico reforça relações assimé-tricas de subordinação, desvalorizando saberes e ações de outros âmbitos da produção do cuidado (tais como o educativo e o preventivo), que se configuram como periféricos ao trabalho nuclear, ou seja, à assistência médica individual 31 . Embora a submissão de profissionais de saú-de a condições laborais frustrantes e desgastantes tenha sido mais descrita em ambientes hospitalares 32,33 , é possível fazer um paralelo com os resultados deste estudo. Descontinuidade no fornecimento de recursos materiais, inadequabilidade de equipamentos e estrutura física 33 podem potencializar fatores de estresse já bastante presentes na dinâmica de trabalho das equipes em condições estáveis, seja na Atenção Básica ou em ambientes hospitalares.…”
Section: Condições De Trabalhofrágil Vínculo/rotatividadeunclassified
“…A insatisfação profissional, associada a ambientes de trabalho negativos, também tem sido apontada como um dos constituintes da Sín-drome de Burnout 28,30,32,34 , que envolve exaustão (perda ou desgaste dos recursos emocionais), despersonalização (sentimentos e atitudes negativas no trabalho) e baixa realização pessoal.…”
Section: Condições De Trabalhofrágil Vínculo/rotatividadeunclassified